2017
DOI: 10.1007/s00414-017-1758-4
|View full text |Cite
|
Sign up to set email alerts
|

Nose profile morphology and accuracy study of nose profile estimation method in Scottish subadult and Indonesian adult populations

Abstract: This study investigated nose profile morphology and its relationship to the skull in Scottish subadult and Indonesian adult populations, with the aim of improving the accuracy of forensic craniofacial reconstruction. Samples of 86 lateral head cephalograms from Dundee Dental School (mean age, 11.8 years) and 335 lateral head cephalograms from the Universitas Padjadjaran Dental Hospital, Bandung, Indonesia (mean age 24.2 years), were measured. The method of nose profile estimation based on skull morphology prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 17 publications
1
12
0
Order By: Relevance
“…Sarilita et al [35] and Utsuno et al [36] was based on different East Asia populations and suggested mostly an overestimated of nasal dimension. Mala [16] and the current study both suggested mostly underestimation of nasal dimensions.…”
Section: Rynn Et Al Suggested Nasal Height and Nasal Depth For Europmentioning
confidence: 99%
See 2 more Smart Citations
“…Sarilita et al [35] and Utsuno et al [36] was based on different East Asia populations and suggested mostly an overestimated of nasal dimension. Mala [16] and the current study both suggested mostly underestimation of nasal dimensions.…”
Section: Rynn Et Al Suggested Nasal Height and Nasal Depth For Europmentioning
confidence: 99%
“…smaller ranges when compared to the European male subjects. Sarilita et al [35] compared the Rynn et al [13] method to an Indonesian population; their results indicated that all measurements were statistically different in both sexes, most measurements (ProAnt, ProFHP, Nasal Length, Nasal Height and Nasal Depth) were overestimated, and ProVert was underestimated.…”
Section: Rynn Et Al Suggested Nasal Height and Nasal Depth For Europmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous methods exist for estimating facial components, including anthropometrical and morphological analysis of the skull. Recently, several studies have been published pertaining to reconstruction of the eyes (Kim et al 2016;Özer et al 2016;Dorfling et al 2018), nose (Strapasson et al 2017;Sarilita et al 2018;Utsuno et al 2018;Bulut et al 2019), and lips (Dias et al 2016;Zednikova Mala and Veleminska 2016). Furthermore, numerous average FSTT datasets have been compiled based on living subjects using a wide range of medical imaging equipment (Drgáčová et al 2016;Parks et al 2017;Sandamini et al 2018;Ayoub et al 2019).…”
Section: The Cfr Techniquementioning
confidence: 99%
“…For instance, significant differences in the symmetric shape component in the nasal region between German and Chinese populations were identified by Schlager and Rüdell (2015), using a dense set of semi-landmarks. An investigation of nose profile morphology in Scottish and Indonesian populations was also carried out by Sarilita et al (2018), with the aim of improving the accuracy of forensic craniofacial reconstruction. The soft-tissue facial form of high-resolution 3D images of Han Chinese, Tibetan, Uyghur and European people was analyzed by Guo et al (2014).…”
Section: Introductionmentioning
confidence: 99%